THE PATTERN OF SUFISM ON INTERPRETATION OF Q.S. AL-FATIHAH IN THE TAFSIR MANUSCRIPT BY M. BASIUNI IMRAN SAMBAS, WEST KALIMANTAN - Parwanto, Wendi; Engku Alwi, Engku Ahmad Zaki; Danoso, Isaac; Reichling, Rukayyah; Gonçalves, Maria Carolina (Universitas Muhammadiyah Surakarta, 2023)
Basiuni Imran is a 20th-century Sambas scholar who once studied with M Rasyid Ridha, so Rasyid Ridha's Islamic reforms ideas were also internalized by M. Basiuni Imran in some of the educational institutions in Sambas. However, in the interpretation, especially the Tafsir of Q.S Al-Fatihah M. Basiuni Imran does not accommodate the value of Islamic reform but interprets it with a Sufistic pattern. On the other hand, no solid information has been found about his Tarekat affiliations or Tarekat tendencies, thus strengthening the indication of his Sufism. Therefore, this research needs to be conducted. This study is library research with a descriptive-analytic model and uses the theory of genealogy and actor networks as an analytical framework. The conclusion of this article explains that the pattern of Sufism narrated by M. Basiuni Imran in interpreting Q.S. Al-Fatihah is by correlating Q.S. Al-Fatihah with Prayers. According to him, prayer is not only done with physical actions but also needs to focus the heart and soul on Allah SWT. He illustrated with the Qibla physically the direction of the Ka’bah is the Qibla during prayer. But in essence, the Qiblah faces the heart to Allah SWT. The factors that influence M. Basiuni Imran's Sufism thought are 1) the relationship of M. Basiuni Imran with some of his Sufism teachers, 2) the socio-religious conditions when writing the interpretation, and 3) the relationship between the book of Sufism and the book of interpretation by M. Basiuni Imran.